A new microfluidic device for separating circulating tumor cells based on their physical properties by using electrophoresis and dielectrophoresis forces within an electrical field. (March 2020) - Dabighi, Ali; Toghraie, Davood
Highlights: Design of a microfluidic device for cell enumeration. Based on impedance change in aperture. capable of separating circulating tumor cells based on their physical properties. Using electrophoresis and dielectrophoresis forces. Abstract: Background and Objective: The presence of circulating tumor cells in the patient's blood is a clinical factor that indicates the initiation of metastasis. Methods: In this paper, a microfluidic device is designed to separate, enumerate, and to diagnose cancer cells from the patient's blood sample. Here, we present a new microfluidic device that is capable of separating circulating tumor cells based on their physical properties by using electrophoresis and dielectrophoresis forces within an electrical field. Cells are modeled as spherical particles, each size as a representor of different cells. Results: The distance between cells has been increased, and by using a novel method of rolling up the convergent and divergent channels, the primary distance of elements, which was 50 µm, reached 142–178.5. Cells with different diameters sense a different force, and therefore, cancer cells can be separating from other cells in the blood, such as white blood cells. To make the current device, practical for clinical studies, a cell enumerator is designed for downstream of cell separator. In the cell enumerator, a change in impedance occurs when a cell passes through the sensor. Conclusions: By measuring the electrical current between two electrodes of the cell enumerator sensor, the exact count of cells can be obtained.